This little chicken went to Africa : a historical survey into the development of narrative structures within relief printmaking in community centres in South Africa and a formal analysis of the relevance of the medium in contemporary children's picture book illustration - Johnson, Shelley (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Visual Arts. Illustration))--University of Stellenbosch, 2009.